Multi Facial Blurring using Improved Henon Map - Saparudin Saparudin; Ghazali Sulong; Muhammed Ahmed Saleh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Generally, full encryption is applied on the entire image to obscure the faces. However, it suffers in overhead, speed and time. Alternatively, selective encryption can be used to encrypt only the sensitive part of the image such as human faces. This paper proposes a new encryption algorithm using enhanced Henon chaotic map to conceal the faces. This technique involves three steps: face detection, encryption and decryption. Experiments have been performed to evaluate security such as histogram, sensitivity and statistical analysis, and results reveal that the proposed method provides high security with entropy and correlation close to ideal values.